2007
DOI: 10.1007/s00280-007-0510-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral versus intravenous dose of vinorelbine to achieve equivalent blood exposures in patients with solid tumours

Abstract: Patient's preference is for oral chemotherapy when both oral and i.v. are available, provided that efficacy is equivalent. Reliable switch from oral to i.v. is possible if correspondence between respective doses has been established. Vinorelbine oral was developed as a line extension of VRL i.v. on the basis that similar AUCs result in similar activities. From a first crossover study on 24 patients receiving VRL 25 mg/m2 i.v. and 80 mg/m2 oral data extrapolation concluded on AUCs bioequivalence between Vinorel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 16 publications
5
33
0
1
Order By: Relevance
“…The linearity of oral VRL pharmacokinetics already shown in the range 60 to 100 mg/m 2 is now confirmed in the lower range of doses (24,26). Low blood concentrations of VRL and DVRL fitted well with the simulated profiles achieved from a previous study and illustrated a continuous and stable exposure to both VRL and DVRL throughout the treatment (19). Achieved in this trial, steady-state concentrations were found in vitro to optimally inhibit proliferation of endothelial cell and induce expression anti-angiogenic molecular effects of endothelial cells (39).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The linearity of oral VRL pharmacokinetics already shown in the range 60 to 100 mg/m 2 is now confirmed in the lower range of doses (24,26). Low blood concentrations of VRL and DVRL fitted well with the simulated profiles achieved from a previous study and illustrated a continuous and stable exposure to both VRL and DVRL throughout the treatment (19). Achieved in this trial, steady-state concentrations were found in vitro to optimally inhibit proliferation of endothelial cell and induce expression anti-angiogenic molecular effects of endothelial cells (39).…”
Section: Discussionsupporting
confidence: 75%
“…The profiles of observed concentrations were in agreement with those simulated using a body surface area of 1.7 m 2 and the dose-adjusted data from a previous study performed at usual dose level (80 mg/m 2 ; ref. 19). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug can be dosed orally or intravenously and inhibits the polymerization of tubulin dimers into microtubules, resulting in the disruption of mitotic spindle formation in dividing cells (Bourgeois et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The absorption of oral vinorelbine is rapid (0.75-3 h) (Bourgeois et al, 2007;Gebbia and Puozzo, 2005;Jehl et al, 1991;Lush et al, 2005) with maximum concentrations (C max ) of approximately 100 ng/mL after administration of 80 mg/m 2 (Gebbia and Puozzo, 2005). After intravenous administration of 25 mg/m 2 much higher C max values of approximately 800 ng/mL were reported (Gebbia and Puozzo, 2005).…”
Section: Introductionmentioning
confidence: 99%